Kinetic and isotherm study of Malachite green dye removal using Imperata cylindrica - Liew, Onn Kei (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
This research encompasses on the adsorption of MG dye from waste water by using Imperata cylindrica (cogon grass) as a low cost adsorbent as compared to chemical adsorbents. Apart from, coagulation and membrane filtration, MG dye is found to be easily extracted from waste water by adsorption. Batch adsorption on cogon grass as a function of various parameters such as solution pH (4-8), initial dye concentration (20- 120 mg/L) and adsorbent dosage (0.1-0.5 g) was studied. Cogon grass leaf-based adsorbent was found effective in MG dye removal where the maximum sorption capacity found to be 30.67 mg/g and the maximum percentage removal was 96.03 %. The optimum condition for the adsorption to occur were at pH 8 with adsorption capacity 29.36 mg/g, 50 mg/L of initial MG dye concentration with adsorption capacity 29.45 mg/g and 0.3 g adsorbent dosage with 27.73 mg/g. The rates of adsorption were found well fitted to pseudo-second order model which has higher-correlation coefficient than pseudo-first order, while equilibrium studies revealed that the adsorption process follow the Langmuir isotherm. The cogon grass leaf-based adsorbent were characterized by scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) spectroscopy. SEM images of cogon grass indicate that it has porous and rough surface that provide micropores for adsorption process occurred. FTIR analysis was showed that formation of chemical bond between functional groups present on cogon grass and MG. Hence, cogon grass leaf powder has a potential to be developed as low cost adsorbent for the removal of the MG dye.